Monetary Policy Channels and Agricultural Performance: Evidence from Nigeria - Asaleye, Abiola John; Maimako, Rotdelmwa Filibus; Lawal, Adedoyin Isola; Inegbedion, Henry; Popoola, Olabisi (Asian Economic and Financial Review, 2021)
The implications of monetary policy on agricultural performance have not been given adequate attention in literature to date, especially in connection with employment and export in the agricultural sector. Determining the right channels of monetary policy can help to achieve sustainable growth in developing economies. This study examines the impact of monetary policy channels on agricultural performance in Nigeria using structural vector autoregression (SVAR) and dynamic ordinary least squares (DOLS). The study uses output employment and export as metrics for agricultural performance, and the channels of monetary policy considered are credit, interest rate, money and exchange rate. The SVAR variance decomposition findings show that the forecast error shocks of monetary policy channels affect agricultural performance. Likewise, the long-run equations from the DOLS show that output has a positive relationship with money supply, a negative relationship between employment and interest rate, and a negative relationship between exchange rate and export. Based on the findings, the study suggests that the Nigerian government should look beyond the primary objective of stabilizing the economy via money supply and interest rate and consider the secondary benefits of bolstering output and employment in the agricultural sector.